Comparison and Analysis of Document Stored Databases (International Journal of Engineering and Computer Science, 2017)
NoSQL (Not Only SQL) technology includes broad variety of different databases technologies that were developed in response tostorage of large volume of user data, handling high access frequency, performance of system and processing of the data.Relational databases were not designed to deal with scalable modern real time applications and agility challenges faced by theseapplications. RDBMS are used in many applications for long time, the data is stored in tabular form and it is stored in meaningfulway, but now there is need to store and manage large amount of data which cannot be handled by traditional relational databases.NoSQL technology is used to overcome this feature of the traditional databases by providing efficient way of storing andmanaging various types of data with huge amount of dataset. In this report performance analysis is done on document orienteddatabases: MongoDB, CouchDB and Cassandra. Document oriented database is category of the NoSQL databases where the datais stored in JSON like files. This makes the database capable of storing huge amount of data anywhere in the disk.